The business administration curriculum of De La Salle University- Aguinaldo : its preparation for entrepreneurship - Lagmay-Hernandez, Virginia. 4 0 16; 5
ABSTRACT: STATEMENT OF THE PROBLEM: The study was undertaken to analyze the Business Administration curriculum of the De La Salle University- Aguinaldo in order to determine its preparation for entrepreneurship. More specifically, this study sought to answer the following questions: 1.
Thesis (Ph.D.) -- Pamantasan ng Lungsod ng Maynila, 1993.;A dissertation presented to the faculty of Graduate School of Arts, Sciences and Education in partial fulfillment of the requirements for the degree Doctor of Education major in Educational Administration.
How do the respondents assess the curriculum in terms of: 1.1 mission statement 1.2 the attainment of the objectives of business education, and 1.3 its usefulness for the preparation of the students to entrepreneurship? 2.
What are the educational qualifications and experiences of the members of the teaching staff in Business Administration? Do they have training background in entrepreneurship? 3.
What are the preparation requirements needed by the students to become entrepreneurs as perceived by the respondents? 4.
There is no significant difference in the perception of the curriculum, in terms of the attainment of the objectives of business education among the following respondents: 1.1 Administrators, 1.2 Faculty, 1.3 Students, 1.4 Graduates, and 1.5 Business Community 2.
There is no significant difference in the perception of the curriculum, in terms of the degree of usefulness for the preparation of the students toward entrepreneurship among the following respondents: 2.1 Administrators, 2.2 Faculty, 2.3 Students, 2.4 Graduates, and 2.5 Business Community. 3.
Keywords: Entrepreneurship program was needed in the nourishment of entrepreneurial skills or abilities of the administrators, faculty, students, graduates, and business community. RECOMMENDATIONS: In the light of the conclusions made, the following recommendations are offered: 1.; Since the group respondents indicated that students preparation should be geared toward the entrepreneurship, a distinct organized curriculum model on entrepreneurial management as a major field should be included in the Business Administration curriculum. The proposed curriculum model is shown in Exhibit I and II. 2.; Strengthen linkages with DLSU-Aguinaldo's Small Business Development Foundation, Inc, (SBDFI) through: a. Attendance in seminars sponsored by SBDFI b. Involvement of students in monitoring livelihood funded projects of SBDFI c. Provision of a regular updates or information on the Small Medium Enterprises (SMEs) management. d. Assistance in fund sourcing by making information available on how capital can be obtained or soft loans be made accessible. 4. To establish a centralized information and communication network with Small Medium Enterprises in CALABARZON and other non-government organizations (NGOs). Government, b